PLURALISME MEDIA: EFEKTIVITAS PRAKTIK DAN TANTANGAN DAKWAH PADA MASYARAKAT KONTEMPORER DI ERA DIGITAl - H T Aman, Siti Nurfadillah (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This research aims to analyze the challenges and opportunities that arise in the era of media pluralism, as well as effective da'wah strategies in the era of media pluralism within contemporary society. This research uses the Library Research method, which involves the analysis of literature relevant to the established research focus. Primary and secondary data were obtained through research on relevant journals that support the research findings. The data collection method was carried out by gathering information and analyzing the media as well as the values of da'wah contained within it. The research results show that with the availability of various media, da'wah practitioners certainly face challenges and opportunities. The challenge of preaching practices in the realm of media pluralism in the digital era is the existence of differing views and beliefs among the community that are recognized and respected in Islam. There are also opportunities for da'wah practices that can be utilized. One of those opportunities is through online media. An effective da'wah strategy requires a careful and well-planned approach to achieve the goals of da'wah